Leadership Style and Employee Performance: Systematic Literature Review - Hasna Hamida Alifia Ar-Rasyi; Sopiah, Sopiah (Ebisnis Manajemen, 2023)
The purpose of this SLR research is to analyze the influence of leadership style and employee performance. The research method used is a systematic literature review using the Preferred Reporting Item Method for Systematic Review and Meta-analysis (PRISMA), data sources were obtained from Google Sciencedirect and Google Scholar from 2019-2023, 285 journals were obtained, the journals were re-selected, the results were 90 journals out of 285 could be accessed. Then according to the title, 10 journals met the requirements. The results showed that leadership is closely related to organizational performance and also employee performance. leadership styles are divided into three types: transactional, transformational, and passive. Transformational leadership style is more often applied because it is associated with high levels of employee performance.